Impact of livestock activity on near-surface ground temperatures in central Mongolian grasslands - R. B. Zweigel; R. B. Zweigel; A. Dashtseren; A. Dashtseren; K. Temuujin; A. Sharkhuu; C. Webster; H. Lee; S. Westermann; S. Westermann (Biogeosciences)
Grazing by livestock can alter the surface conditions at grassland sites, impacting the transfer of energy between the atmosphere and ground and consequentially ground temperatures. In this study, we investigate surface cover in summer and winter and measure ground surface temperatures over 14 months at sites in central Mongolia that feature different grazing intensities (intensely and ungrazed) and topographic aspects (north- and south-facing). Overall, intense grazing leads to a substantially reduced vegetation cover, altered snow conditions, and lack of surface litter accumulation. Comparing intensely grazed and ungrazed plots shows large seasonal differences in ground surface temperatures, with grazed plots being up to +5.1 °C warmer in summer and −5.4 °C colder in winter at a south-facing site. We also find that the effect of grazing intensity depends on topographic aspect, with smaller seasonal differences of +1.4 °C and −2.5 °C found between grazed and ungrazed plots at a north-facing site. This relates to the lower available solar radiation at north-facing sites, which reduces the differences in vegetation cover between open and fenced plots. For both aspects, the seasonal differences largely offset each other, with both a small net cooling and warming depending on effects in spring and autumn. Our study suggests that livestock management could be used to modify the annual ground temperature dynamics, possibly even influencing local permafrost dynamics.